Design of intelligent classroom teaching scheme using artificial intelligence. (14th July 2022) - Su, Yingying
The study aims to improve the efficiency and quality of teaching, improve students' interest in learning and performance. A design scheme of intelligent classroom is proposed based on artificial intelligence technology, which can be divided into online part of personalised learning recommendation and offline part of classroom quality evaluation. First, a multi-layer Back Propagation (BP) neural network combined with genetic algorithm and an actual entropy model is designed to predict students' performance and analyse their learning behaviour. Second, in the design of offline system, the model of You Only Look Once (YOLOv3) is used to design the model of students' concentration detection. Finally, the online system and offline system are combined to realise the functions of students' learning behaviour feature extraction, students' performance prediction, students' learning rule analysis, and students' personalised learning recommendation.